Numerical simulation and application of ground stress field in ultra-deep strike-slip faults—taking the FI12 fault zone in the Fuman Oilfield as an example - Zhang, Yu; Xu, Ke; Zhang, Hui; Lai, Shujun; Liang, Jingrui; Qian, Ziwei (Frontiers in Energy Research, 2024)
This study carried out a research on the distribution characteristics of the geostress field of ultra-deep strike-slip faults, aiming to improve the exploration efficiency and development benefits of ultra-deep fault-controlled reservoirs. This study combines multiple geological information, drilling information, seismic data, and seismic attribute analysis. Taking the FI12 fault zone in the Fengman Oilfield as an example, it carried out numerical simulation of the geostress field, clarified the distribution pattern of geostress, analyzed the effectiveness of fracture mechanics, and proposed a reservoir quality evaluation method and production increase strategy based on geostress analysis. The study includes the following three aspects: (1) research on the heterogeneity of fault-controlled fractured carbonate reservoirs: Due to the existence of faults, fractures, and pores, carbonate reservoirs exhibit strong heterogeneity. These discontinuous structures lead to local stress field decreases to varying degrees. By analyzing the changes in geostress, it is possible to infer the development of faults, fractures, and pores. This provides important basis for predicting and evaluating reservoirs. (2) research on the distribution pattern of geostress: The geostress of fractured bodies exhibits a "shell-type" distribution pattern. Inside the fractured body, the geostress values are lower, indicating that this part is a favorable reservoir body. On the outside of the fractured body, the geostress exhibits high-value concentration, and this part has relatively poor permeability and can be regarded as an unfavorable drilling target. (3) research on the relationship between fault-fracture mechanical activity and reservoir quality and production capacity: Geostress and its influence on fault-fracture mechanical activity are directly related to the quality and production capacity of fault-controlled fractured carbonate reservoirs. When deploying well locations and optimizing well trajectories, geostress factors should be fully considered, and reservoir reformation efficiency should be taken into account to promote single well production increases and reservoir economic devel.